De Ritis‐adjusted AST provides comparable efficacy to lactate dehydrogenase as a biomarker for detection of LVAD hemolysis or thrombosis. Issue 7 (26th March 2022) - Schettle, Sarah; Rosenbaum, Andrew; Goodman, Daniel; Stulak, John
Abstract: Background: Lactate hydrogenase (LDH) is a common biomarker utilized in the detection and monitoring of left ventricular assist device (LVAD) hemolysis and thrombosis. Aspartate aminotransferase (AST) and alanine aminotransferase (ALT) are common laboratory tests that can be used to calculate the De Ritis ratio and the De Ritis adjusted AST. Methods: A retrospective review of LVAD patients was performed to identify three cohorts of patients: those with confirmed pump thrombosis after device exchange, those with LVAD‐related hemolysis who were medically managed without pump exchange, and those who did not meet these criteria and served as the control cohort. Evaluation of AST, AST/ALT ratio (referred to as the De Ritis ratio) as well as AST x (AST/ALT) or the De Ritis‐adjusted AST (DRA) was performed. Results: There were 29 patients who underwent device exchange for thrombosis, 25 patients who were diagnosed with hemolysis and treated medically (clopidogrel ( N = 6), heparin ( N = 13), tirofiban ( N = 8), eptifibatide ( N = 2), and some received more than one of these treatments), and 425 control patients. A qualitatively comparable relative and absolute rise in DRA and LDH were found in both surgically managed pump thrombosis and suspected device‐related hemolysis. Conclusions: Both AST and LDH as well DRA are significantly associated with pump thrombosis ( p < 0.0001 for each). DRA is a potential screening biomarker for hemolysis and device thrombosis in stable left ventricular assist device patients. Abstract : Aspartate aminotransferase (AST) and lactate dehydrogenase (LDH) as well De Ritis adjusted AST (DRA) are significantly associated with pump thrombosis ( p < 0.0001 for each). DRA is a potential screening biomarker for hemolysis and device thrombosis in stable left ventricular assist device patients.